Penerapan dan Analisis Digital Marketing pada Produk Fashion - Sylvia Princesa; Yenni Merlin Djajalaksana (Maranatha University Press, 2021)
In the current digital era, digital marketing is a marketing strategy using digital media to reach customers quickly and widely. About She is a fashion brand located in Bandung that tries to do digital marketing to promote fashion products through social media and websites. We can see website performance with Google Analytics, as well as social media analysis through Instagram Insight and Facebook Insight.